2018
DOI: 10.1111/ijcp.13211
|View full text |Cite
|
Sign up to set email alerts
|

Low serum zinc level: The relationship with severe pneumonia and survival in critically ill children

Abstract: Zinc has both a diagnostic and a prognostic value for children with pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 38 publications
4
33
0
3
Order By: Relevance
“…Zinc supplementation is also effective in decreasing oxidative stress [ 245 , 246 ], in shortening the duration of cold symptoms in adults [ 247 ], and was found to have a direct antiviral effect on RSV [ 248 ], Dengue virus [ 249 ], and coronaviruses [ 250 ]. Lastly, some authors suggested that a combination of chloroquine with zinc might enhance chloroquine’s toxicity on viruses [ 249 , 250 , 251 , 252 ]. Te Velthius et al [ 249 ] reported that the combination of Zn2+ and zinc-ionophores like pyrithione can increase the intracellular Zn2+ concentration, and thus inhibits the replication of SARS-coronavirus (SARS-CoV) and equine arteritis virus in cell culture.…”
Section: Zincmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc supplementation is also effective in decreasing oxidative stress [ 245 , 246 ], in shortening the duration of cold symptoms in adults [ 247 ], and was found to have a direct antiviral effect on RSV [ 248 ], Dengue virus [ 249 ], and coronaviruses [ 250 ]. Lastly, some authors suggested that a combination of chloroquine with zinc might enhance chloroquine’s toxicity on viruses [ 249 , 250 , 251 , 252 ]. Te Velthius et al [ 249 ] reported that the combination of Zn2+ and zinc-ionophores like pyrithione can increase the intracellular Zn2+ concentration, and thus inhibits the replication of SARS-coronavirus (SARS-CoV) and equine arteritis virus in cell culture.…”
Section: Zincmentioning
confidence: 99%
“…In a 2018 study, serum zinc levels were found to be significantly lower among pneumonia pediatric patients admitted to PICU compared with patients admitted to other wards; there was a statistically significant decrease in zinc level in critically ill children complicated by sepsis, mechanically ventilated and fatal cases [ 252 ]. Some studies reported similar duration of hospital stay, time to symptoms resolution, and risk of treatment failure in the intervention and in the control group [ 254 , 255 , 256 , 258 , 259 , 262 , 264 , 265 ], while others described partially positive results.…”
Section: Zincmentioning
confidence: 99%
“…There are some previous studies that investigated the relationship between levels of serum Cu and Zn and prognosis in sepsis or septic shock and demonstrated that the higher mortality was correlated with higher serum Cu and lower serum Zn (29,43), but this correlation was not be found in the research of Ayoglu et al in Turkey (26). In contrast, although the 28-day mortality was not signi cant difference between non-SIMD and SILVSD groups, compared with survivors with septic shock, we discovered that the increased levels of whole blood Cu and the reduced levels of whole blood Zn existed in non-survivors with septic shock, which is consistent with previous studies (29,43). After analysis of the correlations between whole blood Cu and Zn and APACHE-II score and SOFA score by Pearson line correlation, we found whole blood Cu was positively correlated with APACHE-II score and SOFA score and whole blood Zn was negatively correlated with APACHE-II score and SOFA score.…”
Section: Discussionmentioning
confidence: 94%
“…Meanwhile, trace elements including copper (Cu) and zinc (Zn) play signi cant roles in anti-oxidant defence system as they can scavenge oxygen free radicals and prevent oxidative damage. Studies in human patients and animal models shown that lower level of serum Zn was associated with severe pneumonia and sepsis and could increase sensitivity for infection and sepsis (18,19). As for serum Cu, it was reported that people with high levels of serum Cu were liable to suffer from myocardial infarction(MI), hypertension, cancer, chronic obstructive pulmonary disease(COPD) and infection (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, deficiencies in other substrates, including vitamin D and zinc (30,31), have been associated with the development of respiratory tract infections and pneumonia; however, we did not measure the serum levels of these components. Further studies are required.…”
Section: Discussionmentioning
confidence: 99%